AN EMPLOYER’S ABILITY TO SUBSTITUTE A DISCIPLINARY ENQUIRY SANCTION – PART 1 - Siphile Hlwatika; Adriaan van der Walt (Obiter, 2023)
It is common practice for employers to appoint an external chairperson to preside over a disciplinary enquiry which has been convened for purposes of investigating allegations of misconduct against an employee. The external chairperson is ordinarily mandated to decide on guilt, and to the extent that there is a guilty finding, to recommend or impose the appropriate disciplinary sanction.Employers often tend to have expectations that the external chairperson will, after having found the employee guilty of the alleged misconduct, impose a sanction of dismissal depending on the gravity of the alleged misconduct . The expected outcome of dismissal, however, does not always occur. An external chairperson may impose a sanction short of dismissal after considering an employee’s mitigating circumstances. An employer’s dissatisfaction with the disciplinary sanction may result in the employer instituting an internal review process to review the external chairperson’s disciplinary sanction, whilst in other cases, employers may resort to unilaterallysubstituting the external chairperson’s disciplinary sanction with a sanction of dismissal. The employer’s disciplinary code and procedure or the collective agreement regulating the disciplinary procedure in the workplace may or may not make provision for the substitution of the disciplinary sanction. In circumstances where there is no provision for the substitution of the disciplinary sanction, the employer’s conduct of substituting the disciplinary sanction raises questions regarding the applicability of the “double jeopardy” principle which means, in an employment context, that an employee should not be subjected to more than one disciplinary enquiry on disciplinary charges arising from the same set of facts.It is, however, a well established principle that employers who are classified as organs of state can review their own decisions. This includes decisions of chairpersons who are appointed to preside over disciplinary enquiries and further decide on the appropriate disciplinary sanction. In the latter case, and in circumstances where the organ of state is dissatisfied with the disciplinary sanction, itmay institute review proceedings in the Labour Court to review and set aside the chairperson’s decision. This recourse is, only available to organs of state and not private sector employers.This article seeks to determine whether it is permissible for an employer to substitute an external chairperson’s disciplinary sanction, and, if so, the circumstances under which an employer is permitted to do so and the procedure which should be followed in such an instance. The article is written in two parts Part 1 covers the employer’s ability to revisit a disciplinary sanction and Part 2 concentrates on the conflicting judgments involving the South African Revenue Services conduct of substituting disciplinary sanctions, alternative avenues to the unilateral substitution of a disciplinary sanction and the conclusion.